ANALYSIS OF VIEWS ON THE FORMATION OF YOUTH LEGAL CULTURE - Shodiev, Behzod Mirsalimovich (Educational Research in Universal Sciences, 2023)
This article analyzes the level of the legal system in which the legal culture is established in the society, the public’s awareness of this legal system, the citizens’ respect for the law, the implementation of legal norms and the manifestation of the level of obedience to the law.